Brachytherapy boost in anal canal cancer – A GEC ESTRO PDR task force meta-analysis. (March 2023) - Annede, Pierre; Ferre, Marjorie; Kirisits, Christian; Pieters, Bradley R.; Schmid, Maximilian; Strnad, Vratislav; Westerveld, Henrike; Chargari, Cyrus
Highlights: Both PDR and HDR BT provided a high efficacy and good profile tolerance. Significant different dose levels according to the EQD2 model were used. PDR BT still has a crucial role to increase the dose in advanced cases. The place of HDR for large tumors and dose escalation is under investigation. Abstract: Purpose: A meta-analysis is presented comparing clinical outcomes and toxicities between high dose rate (HDR) and pulsed dose rate (PDR) brachytherapy (BT) for anal cancer. Methods and material: Retrospective or prospective clinical trials were identified on electronical databases. Data were collected per Preferred Reporting Items for Systematic Reviews and meta-Analyses guidelines. Pooled effect size for HDR and PDR BT were compared using subgroup analyses. Results: Nine retrospective studies with a total of 481 patients treated were included of which 219 with HDR and 262 with PDR. Significant differences were observed between the two groups for baseline characteristics and treatment. The cumulative proportion of stage T3-T4 was lower in the HDR group, 0.15 [95 % confidence interval (CI) 0.07–0.29] vs 0.27 [95 %CI 0.09–0.57] in the LDR group, p < 0.001. Lower BT doses (in equivalent 2-Gy fraction dose) were given for patients in the HDR group, 11.9 Gy [95 %CI 8.2–15.5] vs 19.5 Gy [95 %CI 15.0–24.0] in the PDR group, p < 0.001. No significant differences were found for clinical outcomes or toxicities. The pooled effect size of the overall survival at 5 years for HDR and PDR was respectively 0.82 [95 %CI 0.70–0.94] and 0.82 [95 %CI 0.73–0.91], p > 0.99. The 5 years local control was 0.86 [95 % confidence interval (CI) 0.81–0.91] and 0.83 [95 %CI 0.77–0.89], p = 0.62. Cumulative toxicity-related colostomy proportion was 0.04 [95 %CI 0.02–0.09] and 0.03 [95 %CI 0.02–0.07], p = 0.85. Conclusion: Both modalities provided a good profile of tolerance and are effective organ conservative strategies for patients with anal canal cancer. In parallel with ongoing developments to better determine the optimal fractionation and dose for HDR-BT treatments, especially in large tumors, PDR BT still has a crucial role for dose escalation strategy in advanced cases.